Growing impact of third-parties in VAT taxation – insights from digital platforms - Robert Zieliński; Emilia Teresa Sroka (Studia Prawnicze KUL)
This article examines the increasing involvement of third parties, particularly digital platforms, in VAT taxation. It discusses the shift from traditional state-centric tax collection to a model where private entities play a crucial role in ensuring tax compliance. It highlights the EU VAT’s “deemed supplier” regimes, which impose increased liability on digital platforms facilitating transactions, and explores the potential advantages and disadvantages of this approach.